UJI MACAM PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL 2 VARIETAS TANAMAN STEVIA (Stevia rebaudiana Bertonii M) - Guzali, Futta Ifnu; Nurhayati, Dewi Ratna; Siswadi, Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2020)
Research on Organic Fertilizer Tests on Growth and Yield of 2 Stevia Plant Varieties (Stevia rebaudiana Bertonii M) "has been conducted from 05 September 2019 to 22 November 2019, located in Tlogodringo Hamlet, Gondosuli Village, Tawangmangu District, Karanganyar District. At an altitude of 18000 masl. This study was to examine the types of organic fertilizer on the growth and yield of 2 varieties of Stevia (Stevia rebaudiana Bertonii M). This study uses a Complete Randomized Block Design (RCBD) consisting of 2 factors: The first factor is the type of organic fertilizer (P), consisting of 5 types, namely: P0: No fertilizer, P1: Cow manure fertilizer, P2: Goat manure fertilizer, P3: Chicken manure fertilizer, P4: Petroganik Fertilizer, The second factor is a variety of varieties (V), which consists of 2 levels, namely: V1 (Jumbo Green), V2 (Super Yellow).